Production of piglets as related to slaughter and growth traits - Matti Puonti (Journal of the Scientific Agricultural Society of Finland, 1983)
Selostus: Porsastuotoksen yhteydestä teuras- ja kasvuominaisuuksiin.
Keywords: sika : jalostus